CitGATA7 interact with histone acetyltransferase CitHAG28 to promote citric acid degradation by regulating the glutamine synthetase pathway in citrus - Xiahui Lin; Shaojia Li; Yanna Shi; Yuchen Ma; Yinchun Li; Haohan Tan; Bo Zhang; Changjie Xu; Kunsong Chen (Molecular Horticulture)
Abstract Organic acid is a crucial indicator of fruit quality traits. Citric acid, the predominant organic acid in citrus fruit, directly influences its edible quality and economic value. While the transcriptional regulatory mechanisms of citric acid metabolism have been extensively studied, the understanding about the transcriptional and epigenetic co-regulation mechanisms is limited. This study characterized a transcription factor, CitGATA7, which directly binds to and activates the expression of genes associated with the glutamine synthetase pathway regulating citric acid degradation. These genes include the aconitase encoding gene CitACO3, the isocitrate dehydrogenase encoding gene CitIDH1, and the glutamine synthetase encoding gene CitGS1. Furthermore, CitGATA7 physically interacts with the histone acetyltransferase CitHAG28 to enhance histone 3 acetylation levels near the transcription start site of CitACO3, CitIDH1, and CitGS1, thereby increasing their transcription and promoting citric acid degradation. The findings demonstrate that the CitGATA7-CitHAG28 protein complex transcriptionally regulate the expression of the GS pathway genes, i.e., CitACO3, CitIDH1, and CitGS1, via histone acetylation, thus promoting citric acid catabolism. This study establishes a direct link between transcriptional regulation and histone acetylation regarding citric acid metabolism, providing insights for strategies to manipulate organic acid accumulation in fruit.